Development of an intracanal mature Enterococcus faecalis biofilm and its susceptibility to some antimicrobial intracanal medications; an in vitro study - Mohamed Saber, Shehab El-Din; El-Hady, Soha A (European Journal of Dentistry, 2012)
Objectives: To develop a mature biofilm of Enterococcus faecalis inside the root canal system and to test its susceptibility to some antimicrobial medications in vitro.Methods: Single rooted premolars were mechanically enlarged, sterilized, and then infected with a clinical isolate of E. faecalis. Biofilm formation and maturation was monitored using SEM. Biofilm bacteria were exposed to Amoxicillin+clavulanate, Ciprofloxacin, Clindamycin, Doxycycline, and calcium hydroxide as intracanal medications for 1 week. Finally bacterial samples were collected, and colony-forming units were enumerated.Results: SEM examination confirmed the formation of a mature biofilm at the end of the incubation period. All the chemotherapeutic agents used were significantly better than Calcium hydroxide in elimination of biofilm bacteria. The antimicrobial effect of Amoxicillin + clavulanate, Ciprofloxacin and Clindamycin was significantly better than Doxycycline (P=.05). However the difference in the antimicrobial effectiveness among them was statistically non-significant (P=.05).Conclusions: The method used for bacterial biofilm development and maturation is reliable and can be used to assess the anti bacterial potential of endodontic materials. Also, the local application of antibacterial agents can be beneficial in resistant cases of apical periodontitis but only after careful culture and sensitivity testing to choose the appropriate agent for the existing flora. (Eur J Dent 2012;6:43-50)
Keywords: Endodontics; E. faecalis; biofilm